Economic Discourse: Anti-Thesis of the Covid-19 Pandemic - Zaenuddin Imam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Indonesia is fighting against Covid-19 by modifying its regional quarantine (lockdown) policy into large-scale social restrictions (PSBB) which are localized according to the level of severity in the province, district, or city. During this pandemic, the world economy and Indonesia experienced a slowdown. The government and strategic assessment institutions predict Indonesia's growth will be low or even negative in 2020. To that end, the Government seeks to schedule a New Normal policy so that the economic impact of the pandemic does not lead to a prolonged crisis. This Writing Method Using descriptive. Descriptive method is a method that aims to describe or provide an overview of the object under study through data or samples that have been collected as they are without analyzing and making conclusions that apply to the public. The pandemic causes a domino effect from health to social and economic problems, including business actors. The government is preparing support for the business world through coordination with BI with OJK with national banks so that business zones, business zones, and real zones can always survive despite sluggish economic activity. The government has allocated a budget of IDR 659.2 trillion as a stimulus to overcome the impact of the pandemic. trillion allocated to six sectors. The total realization until the first week of August was Rp. 151.25 trillion or 21.8% of the ceiling of the National Economic Recovery program. Recovery of various aspects of life after the Covid-19 pandemic is generally carried out in stages. However, the recovery depends on the economic and governance structure set by the local government, there are several steps that need to be taken to achieve a post-pandemic sustainable economic recovery agenda.